INDFØDTE FOLK OG KULTUR: Moderne billeder og bevidste identiteter - Veber, Hanne (Tidsskriftet Antropologi, 1996)
culture - modern images and conscious identities Over recent years public discourse in the West has re-focused the question of indigenous peoples from one where indigenous groups were seen primarily as disadvantaged, marginalized populations to a perspective on indigenous groups as cultures. However, this public discourse embraces its objects through, often distorting, images - in the Baudrillardian sense of a hyperreality of flowing signs. Paradoxically, indigenous peoples then need to adopt to Western images of „their” culture and make them look real, in order to retain political and financial support from the West. Support, gained in this contradictory way, tums into a new mechanism for social control by the West over the indigenous Rest. It is argued that the unfinished business of reimagining the concept of culture often has tended (so far) to merrily subsistute the postmodem consumerist lifestyle notion of culture for a theoretical formulation of a more general applicability. While the former sees culture as a domain of self-creation seemingly liberated from the constraints of social and political structures, the latter is starting to equate culture with a human capacity for empowerment that arises as an aspect of collective social interaction within given political-economic contexts and historical conjunctures. The author ends by calling on the well-meaning advocates who work with and for indigenous peoples to acknowledge that it is not culture but persistent structures of colonialism, asymmetrical power relations, and forces of an overtly non-cultural character such as economical exploitation and violent repression that continue to form the conditioning contexts of the indigenous situation.